2013
DOI: 10.1891/0886-6708.vv-d-12-00029
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Rape Among College Women: A Social Psychological Analysis

Abstract: This article examines social psychological underpinnings of fear of rape among college women. We analyze data from a survey of 1,905 female undergraduates to test the influence of 5 subjective perceptions about vulnerability and harm: unique invulnerability, gender risk, defensibility, anticipatory shame, and attribution of injury. We include 3 sources of crime exposure in our models: past sexual victimization, past noncontact violent victimization, and structural risk measured by age, parent's income, and rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…Hickman and Muehlenard's (1997: 538) study of fear of rape among college women indicated that, although the probability of acquaintance rape victimization was much greater than the probability of stranger rape, 'when women thought about situations in which they fear being raped, they thought primarily about stranger rape'. Hillinski, Pentecost Neeson, and Andrews' (2011: 119) qualitative study of fear of crime among college women similarly showed that fear of rape was associated with general fear of crime among the women studied, but they also noted that 'some women stated that they were not fearful of crime because they were prepared to defend themselves' (also see Pryor and Hughes 2013). Informed by such research, it is suggested that, to lessen the belief that victimization is likely and increase women's confidence in their ability to repel a perpetrator, fear reduction workshops should include accurate information about the low probability of being violently victimized by a stranger (with an emphasis on the low probability of being sexually assaulted by a stranger) and some basic self-defense training.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hickman and Muehlenard's (1997: 538) study of fear of rape among college women indicated that, although the probability of acquaintance rape victimization was much greater than the probability of stranger rape, 'when women thought about situations in which they fear being raped, they thought primarily about stranger rape'. Hillinski, Pentecost Neeson, and Andrews' (2011: 119) qualitative study of fear of crime among college women similarly showed that fear of rape was associated with general fear of crime among the women studied, but they also noted that 'some women stated that they were not fearful of crime because they were prepared to defend themselves' (also see Pryor and Hughes 2013). Informed by such research, it is suggested that, to lessen the belief that victimization is likely and increase women's confidence in their ability to repel a perpetrator, fear reduction workshops should include accurate information about the low probability of being violently victimized by a stranger (with an emphasis on the low probability of being sexually assaulted by a stranger) and some basic self-defense training.…”
Section: Discussionmentioning
confidence: 95%
“…To be afraid of crime is to be feminine (Madriz 1997;Stanko 1989). This fear may be affected by a number of socially constructed perceptions of danger -one common explanation for gender differences in fear of crime is that women's fear of crime is enhanced by the thought that any form of personal victimization could escalate into a sexual assault (Ferraro 1996;Karakus, McGarrell 2013; Pryor and Hughes 2013;Young 1992) -but at the core of such fear are patriarchal power structures (Madriz 1997;Stanko 1989Stanko , 1995.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of civilian women have found that a sense of physical vulnerability significantly increases women's fear of rape [16,35]. Within this sample, women's concern about their physical vulnerability to sexual assault could increase significantly when they heard stories about assaults; experienced sexual harassment, assaults, or near assaults; found themselves isolated from their comrades; or served under unsupportive or even threatening officers.…”
Section: Reinforcing Women's Physical Vulnerabilitymentioning
confidence: 88%
“…This fear is not simply a natural result of women's physical vulnerability. For example, civilian women's fears disproportionately center on rape by strangers even though most rapists are known to those they assault, and disproportionately occur among older, middle-class women even though younger, lower-class women are more at risk [24,35].…”
Section: Introductionmentioning
confidence: 99%